Effects of Eccentric Cycling Performed at Long vs. Short Muscle Lengths on Heart Rate, Rate Perceived Effort, and Muscle Damage Markers. Issue 10 (October 2020) - Peñailillo, Luis; Aedo, Carolina; Cartagena, Mayari; Contreras, Alejandra; Reyes, Alvaro; Ramirez-Campillo, Rodrigo; Earp, Jacob E.; Zbinden-Foncea, Hermann
Abstract : Abstract: Peñailillo, L, Aedo, C, Cartagena, M, Contreras, A, Reyes, A, Ramirez-Campillo, R, Earp, JE, and Zbinden-Foncea, H. Effects of eccentric cycling performed at long vs. short muscle lengths on heart rate, rate perceived effort, and muscle damage markers. J Strength Cond Res 34(10): 2895–2902, 2020—It is possible that the magnitude of muscle damage in eccentric cycling is dependent on seat position that could affect the muscle length changes during eccentric contractions. However, no previous study has investigated the effect of seat position on muscle damage and metabolic demand in eccentric exercise. Thus, this study compared 2 seating positions; seat forward in which knee extensor muscles were stretched longer (LONG) and seat back in which the muscles were stretched shorter (SHORT). Young men performed 30 minutes of eccentric cycling at 80% of maximal concentric power output at either LONG ( n = 10) or SHORT ( n = 10) condition. Heart rate and rate perceived effort (RPE) during exercise, changes in maximal voluntary isometric contraction (MVC) strength of the knee extensors, muscle soreness assessed by a visual analog scale (VAS), and pressure-pain threshold (PPT) before, immediately after, and 24–72 hours after exercise were compared between conditions. Heart rate and RPE were significantly greater in LONG than SHORT group (9.5 and 19.0%, respectively). Post-exercise reduction in MVC was 8.4–14.0% greater in LONG than SHORT group from immediately after to 48 hours after exercise. In addition, VAS was greater in LONG than SHORT group from 48 to 72 hours after exercise, and vastus medialis PPT was greater in SHORT than LONG group from 24 to 72 hours after exercise ( p < 0.05). These results suggest that muscle damage and metabolic demand are greater when seat is set back than forward. Thus, when prescribing eccentric cycling to individuals who are unaccustomed to eccentric cycling, it is better to set the seat far from the pedals.